Hydraulic transmissivity inferred from ice-sheet relaxation following Greenland supraglacial lake drainages - Ching-Yao Lai (Nature Portfolio, 2021)
Hydraulic transmissivity under the 1km-thick Greenland Ice Sheet was inferred by ice-sheet uplift relaxation after rapid lake drainage events. A two-order-of-magnitude increase in hydraulic transmissivity was found throughout the melt season.